PERANCANGAN BUKU PHOTOGRAPHY HUMAN INTEREST PADA PEKERJA DIBAWAH UMUR DITINJAU DARI ASPEK ESTETIKA - BERLIAN AMANDA PUTRI, Dr. M. Nasrul Kamal, M.Sn., (Serupa The Journal of Art Education, 2019)
This work aims to produce a book of photography human interest that inspires the community,  making the book photography human interest in underage workers are reviewed from the aesthetic  aspect that contains the children's experience Underage workers, and created a photography human interest book design work to visualize the social condition of the community under Print media. The planning method performs research and Development steps (R&D), a method of data collection done by observation, interviews, and documentation. The data analysis method used is data analysis of 5 W + 1H. The results of the design show that the book Photography Human Interest Underage  workers is designed with attention to layout design, photography, information that wants to be  delivered as well as possible so that it is easy to understand by readers. With the design of this book is expected to make a target audience grateful for life lived and awareness to parents not to hire a child who is still under-age because it has a bad impact on children's psychology and Also endanger child safety.Keywords: planning, Photography Human Interest, underage worker, aestheticaspect